The NM_033380.2 transcript of the COL4A5 gene contains a variable splice site c.4822–10T>C, which has been identified as a causative factor for Alport syndrome - Liang, Lei; Wu, Haotian; Zhao, Jianrong (Frontiers in Genetics, 2024)
Alport Syndrome (AS) is a genetic kidney disorder characterized by progressive hearing loss and atypical eye symptoms, resulting in a poor prognosis and lack of effective targeted therapy. The primary mode of inheritance is X-linked dominant (XLAS) due to variants in the COL4A5 gene. This study revealed a previously unidentified alternative form of the COL4A5 gene, namely the c.4822-10T>C variant, which was confirmed through in vitro experiments. To investigate the impact of a splicing variant on COL4A5 mRNA production, an in vitro minigene splicing assay was utilized. Additionally, molecular dynamics was employed to predict the ability of α5(IV) to form a triple helix. Results from the experiment revealed that the wild-type (WT) plasmid produced two distinct mRNA products simultaneously. Sequence analysis using the BLAST database revealed a 173-bp deletion in the mRNA sequence of the first product, indicating a potential similarity to the XM_016942897.2 transcript of Pan troglodytes. The second mRNA product of the WT plasmid contained the full sequence of exons 51, 52, and 53, as anticipated. Conversely, the mutant (MT) plasmid generated a single mRNA product with a 173-bp deletion in exon 52, leading to the identification of the mature mRNA expression as NM_033380.2: COL4A5: c.4822_4994del. In the context of nonsense-mediated mRNA decay (NMD), the deletion c.4822_4994 results in the production of a truncated protein, p.His1608*, that terminates prematurely. This truncated protein may disrupt the secondary structure of α5(IV) and potentially cause an abnormal conformation of α345(IV). This study examines the relationship between the variable splicing pattern in the NM_033380.2 transcript of the COL4A5 gene in XLAS patients and the presence of the COL4A5 gene splice variant c.4822-10T>C. Our findings indicate that the c.4822-10T>C splice variant leads to activation of nonsense-mediated mRNA degradation (NMD) and reduced COL4A5 mRNA expression, resulting in inadequate synthesis of the corresponding proteins. This aligns with the patient's immunofluorescence results showing negative α5(IV) chain presence at the glomerular basement membrane, bursa, and tubular basement membrane, confirming the pathogenic nature of c.4822-10T>C.